Informatics Training for Pathology Practice and Research in the Digital Era - Heather T. D. Maness PhD; Linda S. Behar-Horenstein PhD; Michael Clare-Salzler MD; Srikar Chamala PhD (Elsevier, 2020)
Pathology informatics is a relatively new field with limited structured training programs for pathologists, especially for computer programming. Here, we describe our efforts to develop and implement a training program in the department of pathology at the University of Florida to meet these additional needs of current students as well as faculty and staff. Three one-credit courses were created using a flipped classroom design. Each course was assessed with a novel survey instrument, and the impact of the program was further measured 6 months after program completion with interviews of 6 participants and thematic analysis. Course objectives were met but with room for improvement. Major factors that had a positive impact included collaborative learning and real-world practice problems. Also, it improved communication with informatics colleagues as well as job task efficiency and effectiveness. Overall, the program raised awareness of informatics professional development and career path opportunities within pathology.